CRISPR-Switch regulates sgRNA activity by Cre recombination for sequential editing of two loci - Krzysztof Chylinski (Nature Portfolio, 2019)
Inducible genome editing systems often suffer from leakiness or reduced activity. Here the authors develop CRISPR-Switch, a Cre recombinase ON/OFF-controlled sgRNA cassette that allows consecutive editing of two loci.